1998
DOI: 10.1097/00001888-199810000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Can Professionalism Be Measured? The Development of a Scale for Use in the Medical Environment

Abstract: The results are interpreted as an encouraging first step toward the development of a reliable scale that measures professionalism within the environment of medical education and residency training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 0 publications
3
71
0
Order By: Relevance
“…We developed survey items from an extensive review of the literature, and information and measures obtained from professional organizations, such as the AAMC Assessment of Professionalism Project, 1 the ACGME Advancing Education in Medical Professionalism, 2 and the American Board of Internal Medicine Project Professionalism, 23,24 and focus groups that reviewed item content, usability, and feasibility. 25 We conducted 2 focus groups in early 2008 with 15 internal medicine residency graduates.…”
Section: Methodsmentioning
confidence: 99%
“…We developed survey items from an extensive review of the literature, and information and measures obtained from professional organizations, such as the AAMC Assessment of Professionalism Project, 1 the ACGME Advancing Education in Medical Professionalism, 2 and the American Board of Internal Medicine Project Professionalism, 23,24 and focus groups that reviewed item content, usability, and feasibility. 25 We conducted 2 focus groups in early 2008 with 15 internal medicine residency graduates.…”
Section: Methodsmentioning
confidence: 99%
“…Using factor analysis, they identified three aspects of professionalism: excellence, honor/ integrity, and altruism/respect. They concluded that although their preliminary results were encouraging, some measurement components needed additional items (Arnold et al 1998). Following this study, DeLisa et al conducted a study, using a revised version of that questionnaire.…”
Section: Practice Pointsmentioning
confidence: 97%
“…Although a rich array of existing measuring tools can be found in the literature, few of them addresses professionalism as a comprehensive construct. Furthermore, few instruments meet the minimal criteria of content validity and reliability that would support their use for academic assessments (Veloski et al 2005;Blackall 2007); among them, a well known instrument for measuring professionalism in medical training environments is developed by Arnold et al which is a questionnaire consisting of 14 items, each of which reflects a particular component of professionalism as operationally defined by the ABIM (Arnold et al 1998;ACGME 2004). Totally 529 questionnaires filled by the medical students and residents from five institutions in the northeast region of the United States were used in their analysis.…”
Section: Practice Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is fluid in definition and may contain as many as 3 to 7 identifiable factors. 27,28 Professionalism was viewed as evident in all the competencies and a separate scale was used for its assessment (TABLE 2). Seven professionalism factors were identified through the ACGME core competencies and the American Board of Pediatrics Program Directors guide to teaching and assessing professionalism.…”
Section: The Development Of the Rotation Rubricmentioning
confidence: 99%